Finite element model of the temperature increase in excised porcine cadaver iris during direct illumination by femtosecond laser pulses - Sun, Hui (Society of Photo-Optical Instrumentation Engineers, 2012)
In order to model the thermal effect of laser exposure of the iris during laser corneal surgery, we simulated the temperature increase in porcine cadaver iris. The simulation data for the 60 kHz FS60 Laser showed that the temperature increased up to 1.23°C and 2.45°C (at laser pulse energy 1 and 2 µJ, respectively) by the 24 second procedure time. Calculated temperature profiles show good agreement with data obtained from ex vivo experiments using porcine cadaver iris. Simulation results of different types of femtosecond lasers indicate that the Laser in situ keratomileusis procedure does not present a safety hazard to the iris.